Risk of testicular cancer in subfertile men: case-control study - Møller, Henrik (British Medical Journal, 1999)
OBJECTIVE: To evaluate the association between subfertility in men and the subsequent risk of testicular cancer. DESIGN: Population based case-control study. SETTING: The Danish population. PARTICIPANTS: Cases were identified in the Danish Cancer Registry; controls were randomly selected from the Danish population with the computerised Danish Central Population Register. Men were interviewed by telephone; 514 men with cancer and 720 controls participated. OUTCOME MEASURE: Occurrence of testicular cancer. RESULTS: A reduced risk of testicular cancer was associated with paternity (relative risk 0.63; 95% confidence interval 0.47 to 0.85). In men who before the diagnosis of testicular cancer had a lower number of children than expected on the basis of their age, the relative risk was 1.98 (1.43 to 2.75). There was no corresponding protective effect associated with a higher number of children than expected. The associations were similar for seminoma and non-seminoma and were not influenced by adjustment for potential confounding factors. CONCLUSION: These data are consistent with the hypothesis that male subfertility and testicular cancer share important aetiological factors.